A intenção de uso de preservativo: um estudo de adolescentes, comparando gêneros e classes sociais - Eliane Braganca de Matos (2008)
One of the serious social problems faced by young people in Brazil is the unwanted pregnancy and also to contamination by AIDS and sexually transmitted diseases. These threats have provided a great impetus for the study of the factor s involved in the determination of safer sexual behaviour, including the use of condoms. The world has been faced with a threat to health against which the only effective barrier is behavioral, and that, so far, can not be considered 'curable' through medi cal procedures. Therefore, the need to identify and understand the factors involved in making decisions regarding sexual behavior is perhaps one of the largest challenges theories of action and behaviour. Using theoreticalframework as the theory of planned behavior this dissertation sought to test the contribution of new constructs in the explanation of the intended use of condoms by young people. Since the implementation of 804 questionnaires sought is also identify and intentional behavioraldifferences between groups of high and low class and also between groups of men and women. The results point to the significant contribution of the moral standard construct increase in the variance explained the intention to use condoms in the model of the Theory ofPlanned Behavior. It was identified, too, that I intend construct generates greater power of explanation of the model than the constructs intention and we intention as developed the TPB. The analysis of the data raised among adolescents has identified no si gnificant differences between groups of different social class. Moreover, there was significant difference between the groups of men and women, as seen in the final analysis this dissertation.